Management of Santri Discipline: Bullying Prevention and Intervention at Dayah Terpadu Al-Muslimun - Prayoga, M. Aditya; Humairah, Intan; Reihannah, Reihannah; Hamdalah, M. Syukri Rizki (Journal of Educational Research and Practice, 2025)
This study explores bullying at Dayah Terpadu Al-Muslimun, an Islamic boarding school in Indonesia. It focuses on its physical, verbal, and social forms and their impact on students' mental health, academic performance, and social well-being. The research addresses the prevalence of bullying in this religious context, driven by factors such as inadequate supervision, sociocultural differences, and limited awareness of its consequences. This study aims to (1) identify the dynamics of bullying, (2) analyze its effects on Santri, and (3) develop disciplinary strategies to foster a safer, more inclusive school environment. Using a phenomenological approach, qualitative data were collected through semi-structured interviews and observations with eight purposively selected participants (administrators, teachers, and students). Thematic analysis revealed that verbal bullying (e.g., derogatory remarks) and social exclusion were most prevalent, often resulting in emotional distress, disengagement from learning, and isolation. Recommended strategies include integrating anti-bullying education into the curriculum, enhancing supervision in high-risk areas, providing counseling services, and involving parents and the broader community. Challenges include limited resources, cultural acceptance of aggressive behavior, and victims' reluctance to report incidents. By addressing bullying within the unique context of a religious educational institution, this study offers culturally sensitive, practical recommendations for school administrators to cultivate a disciplined yet compassionate learning environment.